Do all patients with HER2 positive breast cancer require one year of adjuvant trastuzumab? A systematic review and meta-analysis. (December 2020) - Stewart, Paul; Blanchette, Phillip; Shah, Prakesh S.; Ye, Xiang Y.; Boldt, R. Gabriel; Fernandes, Ricardo; Vandenberg, Ted; Raphael, Jacques
Abstract: One year of adjuvant trastuzumab is considered the standard treatment for patients with HER2 positive breast cancer. However, a shorter duration of trastuzumab may be associated with reduced costs and side effects. Results from randomized trials with diverse non-inferiority margins comparing one year to a shorter duration of adjuvant trastuzumab are not consistent and have not been systematically reviewed using a non-inferiority meta-analysis approach. We conducted a systematic review and meta-analysis of randomized trials to assess whether a shorter duration of adjuvant trastuzumab was non-inferior to one year of treatment or not. The non-inferiority margin for the meta-analysis was pre-defined as the median of the margins of all the trials included. Data of 11, 376 patients from 5 trials were analyzed. Non-inferiority margins in included studies varied from 1.15 to 1.53 with median of 1.29 for HR of DFS. A shorter duration of trastuzumab was non-inferior to one year of therapy for DFS (HR 1.13, 95%CI 1.03–1.24) but inconclusive for OS (HR 1.14, 95%CI 1.00–1.30). In a subgroup analysis for DFS outcome, shorter therapy was non-inferior in patients with ER positive disease (HR 1.10, 95%CI 0.95–1.28) and those with sequential therapy (HR 0.97, 95%CI 0.75–1.27) and when the duration of treatment was 6 months (HR 1.09, 95%CI 0.98–1.22). Although a shorter duration of adjuvant trastuzumab was non-inferior to one year of therapy for DFS in patients with HER2 positive breast cancer based on our HR margin of 1.29, any benefit of a shorter duration comes at a loss of efficacy with an increase in absolute risk up to 3.9% for 5 year DFS. Whether the potential increased risk is clinically acceptable for the benefits of a shorter duration remains debatable. Highlights: Shorter duration of adjuvant trastuzumab in HER2 positive breast cancer is attractive. Inconsistent results seen from the PHARE and PERSEPHONE trials. Meta-analysis suggests shorter duration of trastuzumab is non-inferior. Highlights need for appropriately chosen and applied non-inferiority margin.